RANCANG BANGUN SISTEM PENANGKAP DAN PEMBACAAN GELOMBANG SEISMIK REFRAKSI UNTUK EKSPLORASI HIDROKARBON - Maison Maison; Faizar Farid; Samsidar; Linda Handayani; Rustan; Jesi Pebrilia; Iful Amri (Prodi Fisika FST UNJA, 2019)
The subsurface data acquisition in seismic eksploration usually using expensive equipment. In this work, a low-cost seismic equipment system has been developed for receive and record seismic wave. This system consist of mikrocontroller and software LabView that connected to PC. The subsurface low signals is recorded by geophone and through the amplifier instrument non-inverting. Then, the digital signals is prosessed by Mikrocontroller and visualize by LabView. Output of seismic measurement using this system design are travel time and amplitude. Travel time is used to modelling density and wave velocity to generate wave model. The expected model can give us value of density and wave velocity to obtain the anomaly. It has been tested using 1 geophone and successfully showed the wave, amplitude, and travel time.